2021
DOI: 10.1091/mbc.e21-03-0097
|View full text |Cite
|
Sign up to set email alerts
|

VPS13D interacts with VCP/p97 and negatively regulates ER- mitochondrial interactions

Abstract: Membrane contact sites (MCSs) between the endoplasmic reticulum (ER) and mitochondria are emerging as critical hubs for diverse cellular events, and alterations in the extent of these contacts are linked to neurodegenerative diseases. However, the mechanisms that control ER-mitochondrial interactions are so far elusive. Here, we demonstrate a key role of vacuolar protein sorting-associated protein 13D (VPS13D) in the negative regulation of ER-mitochondrial MCSs. VPS13D suppression results in extensive ER-mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…VPS13 seems to actively participate in an exchange of the lipids between membranes of organelles in membrane contact sites and impaired VPS13 function results in changes in intracellular protein trafficking between Golgi apparatus, plasma membrane, and endosomes, mitochondria functioning and cytoskeleton organization [153]. Recently, it has been found that ataxia/spastic paraplegia-associated isoform VPS13D is a key regulator of MERCS and VPS13D suppression leads to severe defects in mitochondrial morphology, mitochondrial cellular distribution, and mitochondrial DNA synthesis [154]. Lastly, it has been shown that deficiency or mutation of Vacuolar protein sorting-35 (VPS35), a retromer component for endosomal trafficking, has been linked to familial Parkinson's disease depending on Mfn2 degradation and mitochondrial fragmentation [155,156].…”
Section: Tethering Factorsmentioning
confidence: 99%
“…VPS13 seems to actively participate in an exchange of the lipids between membranes of organelles in membrane contact sites and impaired VPS13 function results in changes in intracellular protein trafficking between Golgi apparatus, plasma membrane, and endosomes, mitochondria functioning and cytoskeleton organization [153]. Recently, it has been found that ataxia/spastic paraplegia-associated isoform VPS13D is a key regulator of MERCS and VPS13D suppression leads to severe defects in mitochondrial morphology, mitochondrial cellular distribution, and mitochondrial DNA synthesis [154]. Lastly, it has been shown that deficiency or mutation of Vacuolar protein sorting-35 (VPS35), a retromer component for endosomal trafficking, has been linked to familial Parkinson's disease depending on Mfn2 degradation and mitochondrial fragmentation [155,156].…”
Section: Tethering Factorsmentioning
confidence: 99%
“…VPS13C mutations cause various forms of early-onset Parkinsonism marked by rapid disease progression and early cognitive impairment (Lesage et al, 2016). d VPS13D negatively regulates ERMCS through interactions with Valosin-containing protein (VCP) (Du et al, 2021). Mutations in VPS13D cause spastic ataxia (SPAX) (Gauthier et al, 2018;Seong et al, 2018).…”
Section: Other Contact Sitesmentioning
confidence: 99%
“…Perhaps one of the most exciting and unexpected results was that the crystal structures of two families of Chorein_N‐domain containing proteins (ATG2 and VPS13) showed that they form channels that facilitate the flow of lipid moieties from one lipid bilayer to another [9,12,13]. The presence of Chorein_N‐domain containing proteins at organelle contact sites, such as the endoplasmic reticulum (ER)‐mitochondria, ER‐lysosome and ER‐phagophore (autophagosome), indicates that lipid transfer between organelles plays an important role in communication between these organelles [7,13–24]. Indeed, the known Chorein_N domain‐containing proteins are large (> 250 kDa) and contain multiple domains that can span organelle contact sites [1–4,15,25,26].…”
Section: The Chorein_n Domainmentioning
confidence: 99%